Minocycline in early Lyme borreliosis - Zöchling, N... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1996)
The present study was performed to assess the efficacy of minocycline in the treatment of early Lyme Borreliosis. 126 patients with erythema migrans were included from june 1993 to april 1995 at the department of dermatology in Graz, Austria. The patients were treated with minocycline 100 mg b.i.d. orally for 14 days and clinically reexamined for 15 months on the average (1 - 30 months). Moreover, a punch biopsy from the erythema migrans lesion was taken in 78/126 patiens to perform borrelia burgdorferi-specific PCR analysis before treatment. A second punch biopsy adjacent to the first biopsy site was able to be obtained in 41/78 patients at the end of therapy. Borrelia burgdorferi-specific PCR yielded positive results in 71% of the patients before therapy. After minocycline treatment, borrelia burgdorferi-specific gene segments were no longer detectable in any of the skin biopsy samples. The good clinical response in conjuction with the PCR data presented indicate the efficacy of minocycline for the treatment of eary Lyme borreliosis. Minocycline is the first antibiotic to be assessed on the molecular in this indication.
Keywords: Adverse effects; Borrelia burgdorferi; Diagnosis; Drug therapy; Follow-up studies; Isolation and purification; Lyme disease; Middle age; Minocycline; Therapeutic use